Late Toxicity After Adjuvant Conventional Radiation Versus Image-Guided Intensity-Modulated Radiotherapy for Cervical Cancer (PARCER): A Randomized Controlled Trial. Issue 33 (20th November 2021) - Chopra, Supriya; Gupta, Sudeep; Kannan, Sadhana; Dora, Tapas; Engineer, Reena; Mangaj, Akshay; Maheshwari, Amita; Shylasree, T. Surappa; Ghosh, Jaya; Paul, Siji N.; Phurailatpam, Reena; Charnalia, Mayuri; et al.
Abstract : PURPOSE: Postoperative Adjuvant Radiation in Cervical Cancer (PARCER), a phase III randomized trial, compared late toxicity after image-guided intensity-modulated radiotherapy (IG-IMRT) with three-dimensional conformal radiation therapy (3D-CRT) in women with cervical cancer undergoing postoperative radiation. METHODS: Patients were randomly assigned to receive either IG-IMRT or 3D-CRT after stratification for the type of hysterectomy and use of concurrent chemotherapy. The primary end point was 3-year grade ≥ 2 late GI toxicity assessed using Common Toxicity Criteria for Adverse Events v 3.0 and estimated using time-to-event, intention-to-treat analysis, with a study level type I error of 0.05 and a nominal α of .047 after accounting for one interim analysis. Secondary end points included acute toxicity, health-related quality of life, and pelvic relapse-free, disease-free, and overall survival. RESULTS: Between 2011 and 2019, 300 patients were randomly assigned (IG-IMRT 151 and 3D-CRT 149). At a median follow-up of 46 (interquartile range, 20-72) months, the 3-year cumulative incidence of grade ≥ 2 late GI toxicity in the IG-IMRT and 3D-CRT arms were 21.1% versus 42.4% (hazard ratio [HR] 0.46; 95% CI, 0.29 to 0.73; P < .001). The cumulative incidence of grade ≥ 2 any late toxicity was 28.1% versus 48.9% (HR 0.50; 95% CI, 0.33 to 0.76; P < .001), respectively. Patients reported reduced diarrhea ( P = .04), improved appetite ( P = .008), and lesser bowel symptoms ( P = .002) with IG-IMRT. However, no difference was observed in the time by treatment interaction. The 3-year pelvic relapse-free survival and disease-free survival in the IG-IMRT versus the 3D-CRT arm were 81.8% versus 84% (HR 1.17; 95% CI, 0.68 to 1.99; P = .55) and 76.9% versus 81.2% (HR 1.03; 95% CI, 0.62 to 1.71; P = .89), respectively. CONCLUSION: IG-IMRT results in reduced toxicity with no difference in disease outcomes.